الضمانات التشريعية لمبدأ المساواة في الحملات الإنتخابية بعد دستور2020 - الساكر, عماد الدين (University of Eloued جامعة الوادي, 2022)
تهدف د ا رستنا التي تتمحور حول الحملة الانتخابية في ظل القانون الجديد الى انه من خلال تعدد المترشحين في الانتخابات يشتد التنافس بينهم , فكل مترشح يحاول ان يبرز نفسه بالإعلان عن برنامجه ومقترحاته السياسية وفق مايقتضيه القانون وكذلك ما يع رف بالحملة الانتخابية ولكي لا تعم الفوضى وضع المشروع الج ا زئري مجموعة من القوانين لتنظيمها من توقيت ومدة الحملات الانتخابية وكما تهدف هذه الد ا رسة الى تسويق الحملات الانتخابية مع تحديد عوامل نجاح الانتخابات والتي يجب ان تكون مسلمة ونزيهة والا كنا امام منازعات في القائمة الانتخابية. وفي الأخير توصلنا الى ان الحملة الانتخابية تتم وفق است ا رتيجيات وأساليب محددة وفي مدة معينة وفي ظل مايقتضيه القانون الانتخابي.Our study, which revolves around the election campaign under the new law , aims to that through the multiplicity of candidates in the elections is highly competitive among them , each candidate tries to highlight himself by announcing his program and political proposals as required by law as well as what is known as the election campaign and in order not to be chaotic the Algerian legislator put a set of laws to organize them from the timing and duration of election campaigns and as this study aims to market campaigns while identifying the factors of electoral success which must be Muslim and fair otherwise we would be facing disputes on the electoral list . In the end, we have concluded that the election campaign is conducted in accordance with specific strategies and methods, in a certain period and under the requirements of the electoral law
مذكرة ماستر
Keywords: الضمانات التشريعية- لمبدأ المساواة- الحملات الإنتخابية- الدستور; Legislative guarantees - the principle of equality - electoral campaigns - theconstitution